Towards the attainment of self-sustaining growth: Ghana and the Ivory Coast - Sven Heldt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1977)
Ghana and the Ivory Coast are two neighbouring states of the West Coast of Africa so similar in size, geography, resource endowment, stage of economic development in terms of per capita income and capacity to develop at the date of independence (Ghana 1957 and Ivory Coast 1960), that a comparison of the results of the economic policies adopted and the political orientation followed by each of them has ever been a big challenge. While Ghana had at the time of independence almost twice the population of Ivory Coast, the agricultural sector had similar importance accounting for more than 40 percent of GDP, the industrial sector for less than 10 percent. The principal agricultural export crops were the same: cocoa, coffee and wood and the importance of external trade was also similar, amounting to about 30 percent of GDP in each country in 1960 (table 1). But while in Ghana cocoa was by far the most important export product it was coffee in the case of Ivory Coast.
Keywords: 330